Analisis Hukum Terkait Kondisi Pembatalan dalam Perjanjian Jual-Beli Daring Berdasarkan Prinsip Hukum Kontrak dan Implementasi Undang-Undang Perlindungan Konsumen Nomor 8 Tahun 1999 - Bambang Tresno Wahyudi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The main objective of this study is to examine whether agreements reached in electronic transactions through online shopping platforms comply with the fundamental principles of contract law. The principles tested include the principle of freedom of contract, the principle of consensualism, the principle of pacta sunt servanda, and the principle of good faith. In addition, this study also aims to understand the legal protection framework for consumers in the context of digital transactions. The methodology applied in this study is normative law, using an approach that focuses on legislation and a conceptual approach. The legal material used consists of primary, secondary, and tertiary legal materials. The collection of legal material was carried out through a literature study, which was then analyzed using deductive logic.Based on the results of the research and data analysis, it was concluded that agreements formed in electronic transactions through online shopping sites have fulfilled the principles of freedom of contract, consensualism, pacta sunt servanda, and good faith. Legal protection for consumers in e-commerce transactions has been adequately provided through the regulation of Law Number 11 of 2008 concerning Electronic Information and Transactions and Law Number 8 of 1999 concerning Consumer Protection.